Evaluating the influence of COVID-19 pandemic lockdown on Jordan Badia rangelands. Issue 4 (2nd October 2021) - Sawalhah, Mohammed N.; Othman, Yahia A.; Abu Yahya, Anas; Al-Kofahi, Salman D.; Al-Lataifeh, Fatima A.; Cibils, Andres F.
Abstract: To explore the effect of COVID-19 pandemic lockdown on vegetation cover changes in Northern, Middle, and Eastern Jordan Badia rangelands, Landsat-8 (Operational Land Imager [OLI]) images were downloaded and processed to attain surface reflectance data for March and July 2018–2020. Normalized difference vegetation index (NDVI) was then derived from OLI-images, where the total area covered with water, bare soil, scattered vegetation, dense grasses and shrubs, and dense forests were estimated. Across the study period, 2019 had the highest rainfall (195 mm) and temperature (21.7 °C), while the lowest rainfall was recorded in 2018 (154 mm). The Northern Badia showed a consistently larger area of dense vegetation on average (407.4 km 2 ) compared to the Eastern (149.3km 2 ), and Middle (55.2 km 2 ) Badia. The total area covered with scattered vegetation in 2020 was higher than in 2019 and 2018 across the years and studied area, except in Middle Badia. Vegetation cover classes were inconsistent for Middle Badia in March, scattered vegetation was higher in 2019 compared to 2020. However, the total area covered with vegetation in July was lower than in March across the years and studied area. The curfew allowed the regeneration of shrubs and grasses in the study area, which helped in restoring the rangeland vegetation. COVID-19 lockdown served as a conservation grazing technique and provided a real case of restoring the degraded rangeland cover through managed grazing.